PLD.42 'Sepsis Six' – Adaptation of a trust innovation in Maternity. (9th June 2014) - Deutsch, L; Aggarwal, R; Wright, A; Stapleton, C; Stanley, S; Emerson, M
Abstract : Introduction: Sepsis was the leading cause of maternal death in the 2006–2008 Confidential Enquiry, 1 which led the development of the RCOG Guideline recommending early treatment to reduce morbidity and mortality. 2 Following a death from severe sepsis at the Royal Free Hospital in 2009, the 'Sepsis Six' Protocol was designed and implemented by the Trust Board. An 8% reduction in mortality, with 20% increased survival secondary to sepsis 3 in other hospital departments, inspired adaptation of this protocol for Maternity in October 2013. Intervention: Patients requiring implementation of 'Sepsis Six', trigger if two or more objective parameters are abnormal (Temp <36°C or >38°C, SBP < 90 mmHg; HR ≥ 125 bpm; RR ≥ 25 bpm, GCS < 15; Oliguria (<0.5 ml/kg over 2 h); pH < 7.25; lactate > 4). This prompts a care package of six management steps (oxygen, IV antibiotics, IV fluid challenge, septic screen, venous lactate, fluid balance monitoring). A multi-disciplinary team adapted 'Sepsis Six' for obstetric patients to include recognition of obstetric sources of sepsis, restricted fluid resuscitation for pre-eclamptic women and introduction of an obstetric antibiotic guideline. Results: Since implementation, ten patients have met criteria for initiation of 'Sepsis Six' management; 50% achieved all interventions within one hour. All women were managed appropriately by the multi-disciplinary team and discharged home. Conclusion: This pilot reflects lessons learnt from elsewhere in the hospital can lead to innovations in maternity. In the future, we hope to emulate the >95% compliance for initiation of interventions within one hour, which has been achieved in other areas of the hospital. References: Centre for Maternal and Child Enquiries (CMACE). Saving Mother's Lives: reviewing maternal deaths to make motherhood safer: 2006–2008 BJOG 2011; 118(suppl. 1): 1–203 London: RCOG Press; 2007 Royal College of Obstetricians and Gynaecologists Green Top Guideline No 64A: Bacterial Sepsis in Pregnancy, 1 st edition, April 2012 Severe Sepsis Improvement Group, Royal Free Hospital, data review 2009–2013 (Jan 2014)